2001
DOI: 10.1002/bit.1106
|View full text |Cite
|
Sign up to set email alerts
|

Choline‐binding domain as a novel affinity tag for purification of fusion proteins produced in Pichia pastoris

Abstract: The choline-binding domain (ChoBD) of the carboxy-terminal region of the Streptococcus pneumoniae amidase LYTA (C-LYTA) presents a strong affinity for tertiary amines. We report a method for single-step purification of proteins expressed in the methylotrophic yeast Pichia pastoris based on the fusion of C-LYTA to the protein of interest. We show that C-LYTA can be efficiently expressed and secreted in this host. Tagged proteins fused to this binding domain can be purified on inexpensive DEAE matrices. It there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
(23 reference statements)
0
11
0
1
Order By: Relevance
“…To assess whether lysin SMl demonstrated its predicted biological activities, we first examined its binding to DEAE-cellulose, a property that is a hallmark of choline-binding proteins [21]. Lysin SM1 , N-lysin SM1 , and C-lysin SM1 were expressed individually in Escherichia coli , and lysates from these strains were applied to a DEAE-cellulose column [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess whether lysin SMl demonstrated its predicted biological activities, we first examined its binding to DEAE-cellulose, a property that is a hallmark of choline-binding proteins [21]. Lysin SM1 , N-lysin SM1 , and C-lysin SM1 were expressed individually in Escherichia coli , and lysates from these strains were applied to a DEAE-cellulose column [16].…”
Section: Resultsmentioning
confidence: 99%
“…The bacteria were incubated with purified FLAG lysin SM1 (0 to 10 µg/ml) for 30 min at room temperature. The samples were washed twice with PBS to remove unbound FLAG lysin SM1 and incubated with PBS-2% choline chloride to elute choline-binding proteins from the cell walls, as described previously [21]. Eluted cell wall proteins were harvested by centrifugation and loaded onto SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…Both PblA and PblB contain repeat regions of glycine‐tryptophan‐rich motifs, similar to the choline binding proteins of S. pneumoniae , and the lipoteichoic acid binding regions of InlB of Listeria monocytogenes (Jonquieres et al ., 1999). Moreover, we have shown that PblA and PblB can be purified from culture media by affinity chromatography with DEAE cellulose (a choline analogue), as has been done with other choline binding proteins (Sanchez‐Beato et al ., 1995; Caubin et al ., 2001; Fan et al ., 2004; Moldes et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To get this, we made use of the affinity tag CLytA, which is the choline-binding module of the amidase N-acetylmuramoyl-L-alanine (LytA) from Streptococcus pneumoniae [15]. The CLytA domain shows high affinity for choline and choline structural analogs, such as diethylaminoethanol (DEAE), and it is routinely used as an affinity tag for the single-step purification and immobilization of fusion proteins [16][17][18].The chimera was specifically immobilized onto MNPs functionalized with DEAE. Both, free and immobilized, CLytA-DAAO chimera are able to induce cell death by increasing ROS production, which caused DNA damage in several colon carcinoma and pancreatic adenocarcinoma cell lines as well as in glioblastoma cell lines derived from primary cultures obtained in our laboratory directly from glioblastoma patients, at doses that are safe for non-tumor cells.…”
mentioning
confidence: 99%